The role of affective empathy in eliminating discrimination against women: a conceptual proposition - Guthridge, Michaela (Human rights review, 2023)
Due to its wide-ranging reservations and lack of effective enforcement mechanisms the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) has failed to dismantle widespread and systemic discrimination. The present paper proposes a broad, theoretical, preventive and relational approach to creating and enhancing the effectiveness of novel interventions to accelerate gender equality. We describe the main elements of affective empathy (i.e. intersubjectivity, multisensory engagement and empathic embodiment) and identify potential interventions that build on those elements to advance gender equality. We ultimately argue that increased empathy towards women, transwomen and girls is required to disrupt the beliefs and behaviours that lead to discrimination, and that these changes must be enacted alongside legislative reforms and community education that construct equality environments. Our affective empathy framework could have the capacity to operationalise the normative fight against gender stereotypes and inequality in line with article 5(a) of CEDAW.